2011
DOI: 10.2169/internalmedicine.50.4198
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Left Atrium-Coronary Sinus Musculature Electrical Connection at Coronary Sinus Ostium Unmasked by Unique Double Coronary Sinus Potentials Pattern

Abstract: We describe a 77-year-old man with Wolff-Parkinson-White syndrome exhibiting double coronary sinus (CS) potentials during retrograde conduction over accessory pathway (AP). The first, low-frequency potential (DP1) was first recorded in the left posterolateral region, while the second, higher frequency signal (DP2) was recorded in a lateral-to-septal direction. The two signals were fused near the left lateral wall. Successful ablation of the AP was obtained at its ventricular insertion site in the postero-septa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…B and B). Such a long conduction pathway was formed because of the absence of LA–CS musculature connection in the proximal CS, which is consistent with that in the case reported by Saito et al …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…B and B). Such a long conduction pathway was formed because of the absence of LA–CS musculature connection in the proximal CS, which is consistent with that in the case reported by Saito et al …”
Section: Discussionsupporting
confidence: 90%
“…1B and 3B). Such a long conduction pathway was formed because of the absence of LA-CS musculature connection in the proximal CS, which is consistent with that in the case reported by Saito et al 4 LA and right atrium (RA) are connected electrically to each other at the level of the Bachmann's bundle, interatrial septum, and CS musculature. 1 If electrical activation from the left posteroseptal accessory pathway was preferentially conducted to RA through the Bachmann's bundle or interatrial septum, the above-mentioned conduction pathway could not be formed.…”
Section: Discussionsupporting
confidence: 89%
“…Kasai et al first reported that the far‐field LA and near‐field CSM potentials recorded from the CS, which seemed to be fused, could be separated by functional block over the CSM → LA connection caused by extrastimulation [9]. We reported the recording of double CS potentials, consisting of LA and CSM potentials, visible only during retrograde AP conduction in patients in whom there were few LA → CSM connections, except in the proximal CS [7,10]. The activation pattern of the double potentials varies, depending on the differences in the conductive properties of the LA‐CSM connections [7,10,11].…”
Section: Discussionmentioning
confidence: 80%
“…We reported the recording of double CS potentials, consisting of LA and CSM potentials, visible only during retrograde AP conduction in patients in whom there were few LA → CSM connections, except in the proximal CS [7,10]. The activation pattern of the double potentials varies, depending on the differences in the conductive properties of the LA‐CSM connections [7,10,11]. Double potentials were also recorded inside the CS during atrial fibrillation, and during typical or perimitral AFL in patients with LA → CSM connections that were impaired by an ablation attempt [11–14].…”
Section: Discussionmentioning
confidence: 99%